Skin Involvement of Mantle Cell Lymphoma May Mimic Primary Cutaneous Diffuse Large B-cell Lymphoma, Leg Type. (August 2015) - Wehkamp, Ulrike; Pott, Christiane; Unterhalt, Michael; Koch, Karoline; Weichenthal, Michael; Klapper, Wolfram; Oschlies, Ilske
<x xml:space="preserve">Abstract</x> Mantle cell lymphoma (MCL) is a B-cell neoplasm with a variable and generally aggressive clinical course. So far our knowledge of skin involvement of MCL is limited. To understand the clinical and histopathologic features of MCL with skin involvement, the files of the Lymph Node Registry Kiel were screened for MCL diagnosed in the skin. Over a period of 13 years, 1321 biopsy specimens were diagnosed as MCL; among them, 14 patients (1%) showed skin involvement. Of these, skin was the initial site of manifestation in 6/11 (55%) cases. One patient presented with a skin-limited lymphoma. Furthermore, 7/12 (58%) patients presented with lesions on the leg. The lymphomas were highly proliferative with blastoid cytology in 12/14 (86%) cases. Moreover, the immunophenotype with expression of BCL2 (100%), MUM-1/IRF4 (83%), and IgM (82%) and lack of CD10 (25%) and BCL6 (0%) closely resembled the features of primary cutaneous diffuse large B-cell lymphoma, leg type. Solely the expression of cyclin D1 (100%) and the presence of t(11;14) (100%) allowed a distinction from cases of primary cutaneous diffuse large B-cell lymphoma, leg type. Only 2 MCL cases with skin involvement presented with classical cytology. Interestingly, in these 2 cases skin involvement occurred simultaneously in a lesion of coexisting primary cutaneous marginal zone lymphoma. Our data suggest that clinical presentation on the leg and blastoid cytology along with high proliferation and expression of Bcl2, Mum-1/IRF4, and IgM are typical for MCL involving the skin. Lymphomas with these features might be erroneously diagnosed as diffuse large B-cell lymphoma, leg type, if cyclin D1 staining is not performed.